NOVA: The Virtual Desktop Assistant - Atharva Vijay Padalkar (International Journal of Computer Science Languages, 2025)
This research work details the design, development, and implementation of a voice-controlled desktop assistant aimed at streamlining everyday tasks and boosting user productivity. The assistant seamlessly integrates with various desktop applications and core operating system functions to automate routine operations, deliver relevant contextual information, and provide personalized suggestions based on observed user behavior and preferences. A standout feature of the system is its ability to monitor user activity levels and detect signs of prolonged engagement or fatigue. When such patterns are identified, the assistant can recommend short breaks and, upon receiving a voice command, automatically play a user-curated playlist tailored to their mood or current activity. This personalized music feature enhances relaxation and overall satisfaction, adapting intelligently to individual needs. Additionally, the study explores the system’s underlying architecture, major functionalities, and the methodology used for performance evaluation. Results from the assessment reveal the assistant’s strong potential in increasing efficiency while promoting a healthier and more balanced digital work environment.
Keywords: Operating system; User experience; User productivity; desktop integration; personal assistant; user satisfaction; voice command